The neurotoxicity of DE‐71: effects on neural development and impairment of serotonergic signaling in zebrafish larvae. Issue 12 (22nd March 2016) - Wang, Xianfeng; Yang, Lihua; Wang, Qiangwei; Guo, Yongyong; Li, Na; Ma, Mei; Zhou, Bingsheng
Abstract: The underlying mechanism of polybrominated diphenyl ether (PBDE)‐induced neurotoxicity is still a major concern due to its ubiquitous nature and persistence. Here, zebrafish embryos (2 h postfertilization, hpf) were exposed to different concentrations of the commercial PBDE mixture DE‐71 (0–100 µg l –1 ) until 120 hpf, and the impact on neural development and serotonergic system was investigated. The in vivo results revealed significantly reduced transcription of genes involved in neurogenesis ( fgf8, shha, wnt1 ), and contents of proteins in neuronal morphogenesis (myelin basic protein, synapsin IIa), suggesting an impairment of neural development in zebrafish embryos. Further results demonstrated a reduction of 5‐hydroxytryptamine neuron and a dose‐dependent decrease of whole‐body serotonin levels, as well as the transcription of genes involved in serotonergic synthesis ( tph1, tph2, trhr ) and neurotransmission ( serta/b, htr1aa/b ). In addition, we predicted possible targets of PBDEs by molecular docking, and the results indicated that PBDE congeners showed high binding affinities with fibroblast growth factor 8 other than SHH and HTR1B. Taken together, this study demonstrated that PBDE exposure during embryogenesis could damage neural development and cause impairment of the serotonergic system as secondary effects in the zebrafish larvae. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Polybrominated diphenyl ethers have been proven to damage the central nervous system and affect neurobehavior in animals, but the underlying mechanism is still not clear. In our study, it was suggested that DE‐71 exposure could cause impairment of the neural development and secondary effects on serotonergic system, and these lesions might be involved in the altered locomotor behavior in zebrafish larvae.